2007
DOI: 10.1186/1471-2474-8-43
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the effect of parenteral naloxone, alone and in association with calcium gluconate, on bone healing in an ovine "drill hole" model system

Abstract: BackgroundSeveral diseases affect bone healing and physiology. Many drugs that are commonly used in orthopaedics as "analgesics" or anti-inflammatory agents impair bone healing. Stressful conditions are associated with decreased serum osteocalcin concentration. High endorphin levels alter calcium metabolism, blocking the membrane channels by which calcium normally enters cells. The consequent decrease of intracellular calcium impairs the activities of calcium-related enzymes. Naloxone is a pure opioid antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
8
0
5
Order By: Relevance
“…The administration of naloxone to OVX rats increased the fracture point load in cancellous bone of the tibial metaphysis; in NOVX rats, there was an increase in the femur mineralization. The improvement of some bone parameters induced by naloxone in rats is consistent with the effect of administration of low-dose naloxone in the sheep: increased mineralization and callus remodeling in a model of bone damage (Petrizzi et al 2007). However, the reports on effects of opioid receptor antagonists on bone resorption are inconsistent; naltrexone caused a decrease of orthodontic tooth movement in rats with experimentally induced cholestasis (Nilforoushan et al 2002), and the topical application of naloxone intensified alveolar bone loss in experimentally induced periodontitis in rats (Queiroz-Junior et al 2013).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The administration of naloxone to OVX rats increased the fracture point load in cancellous bone of the tibial metaphysis; in NOVX rats, there was an increase in the femur mineralization. The improvement of some bone parameters induced by naloxone in rats is consistent with the effect of administration of low-dose naloxone in the sheep: increased mineralization and callus remodeling in a model of bone damage (Petrizzi et al 2007). However, the reports on effects of opioid receptor antagonists on bone resorption are inconsistent; naltrexone caused a decrease of orthodontic tooth movement in rats with experimentally induced cholestasis (Nilforoushan et al 2002), and the topical application of naloxone intensified alveolar bone loss in experimentally induced periodontitis in rats (Queiroz-Junior et al 2013).…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown that naloxone in small doses has an analgesic effect in humans and animals (Petrizzi et al 2007). Due to the enormous complexity of the endogenous opioid peptide system, and opioid receptors, it is possible that the use of naloxone at a particular dosage may differentially modify the action of individual peptides.…”
Section: Discussionmentioning
confidence: 99%
“…While there are relatively few studies that have examined the effect of sustained administration of opioid agonists or antagonists on bone injury/repair/healing, the few publications that have addressed this issue are conflicting. Some studies suggest that opiate agonists are associated with accelerated bone and tissue healing while others suggest the opposite (Poonawala et al, 2005, King et al, 2007, Petrizzi et al, 2007, Zagon et al, 2007). However, one area where there is significant agreement is that opioids do have a variety of non-skeletal side effects that can indirectly inhibit bone healing (Ensrud et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In studies that have examined the effects that opiate agonists and antagonists have on malignant bone remodeling and soft tissue repair the results are controversial. Thus, whereas some studies suggest that opiate agonists stimulate bone and tissue healing (Poonawala et al, 2005) and opiate antagonists accelerate bone and tissue healing (Petrizzi et al, 2007; Zagon et al, 2007) other studies suggest the opposite (King et al, 2007). However, one area where there is nearly complete agreement is that opioids have a variety of CNS side effects that can indirectly inhibit bone healing.…”
Section: Fracture Pain: Causes Consequences and Therapeutic Oppormentioning
confidence: 99%